Barriers to Implementing English-Medium Instruction in Community Schools of Rural Nepal - Karki , Tek Mani; Karki, Rita Devi (Education Quarterly, 2024)
In Nepal, there is a growing trend of adopting the English-mediuminstruction (EMI) policy in community schools; however, some schools are withdrawing it. This study investigates the reasons for rejecting the EMI policy in school-level education in Nepal, focusing on two rural community basic schools in Lalitpur district that discontinued EMI implementation. Using a qualitative case study design, data were collected through interviews with head teachers, teachers, local education policymakers, and informal interactions with the School Management Committee and Parent Teacher Association chairpersons. Thematic analysis with ATLAS. ti highlighted significant issues: the schools serving disadvantaged communities lacked financial resources, making EMI inappropriate. Insufficient English proficiency among teachers and students posed major challenges, and parental support was minimal. The study concludes that successful EMI implementation requires thorough planning, contextual analysis, and stakeholder involvement. It emphasizes adapting EMI policies to local contexts and improving language proficiency to ensure effective implementation in diverse educational settings.